Actualization of Learning Management in Increasing The Effectiveness of Memorization at The Tahfidz Tarbiyatul Qur’an Lawang Islamic Boarding School - Zulvani, Nadia Vina; Wiyono, Bambang Budi; Ubaidillah, Aan Fardani (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
This study explores the actualization of Tahfidz Al-Qur'an learning management in the Tarbiyatul Qur'an Lawang Islamic Boarding School, focusing on internal and external factors influencing its effectiveness. Utilizing a qualitative case study approach, data collection was conducted through interviews, observations, and documentation. The research findings reveal that the planning, organizing, implementing, and evaluation processes are systematically and structurally applied, emphasizing methods like talaqqi and muraja’ah. These approaches enhance the quality and quantity of memorization while maintaining student motivation and discipline. Notably, teacher responsibilities are carefully divided based on experience and expertise, with students grouped according to their memorization level, ensuring personalized and efficient learning. This research highlights critical supporting factors, such as parental involvement and strong self-motivation among students, while also addressing challenges like psychological pressure and inconsistent external support. Unlike previous studies, which primarily examined general educational management, this study delves deeply into the unique contextual factors shaping Tahfidz learning in Islamic Boarding School. The findings contribute a novel perspective on optimizing Islamic boarding school education, particularly by proposing structured and adaptive strategies that balance traditional memorization techniques with modern pedagogical practices. The implications of this research extend beyond the specific context of Islamic Boarding School Tahfidz Qur’an Tarbiyatul Qur'an, offering valuable insights for Islamic boarding schools worldwide facing similar challenges. Future research is recommended to explore the integration of technological tools in Tahfidz learning and the role of psychological support in sustaining student engagement.